The contribution of profit company on education in Indonesia: An analysis of character education management in public elementary school - Nuraini, Sevita Dwi; Rukiyati, Rukiyati; Putera, Agustian Ramadana (Journal of Educational Management and Instruction (JEMIN), 2023)
This research is qualitative research that aims to investigate how the profit cooperation between Astra International in 3 public elementary schools at Special Regency of Yogyakarta specifically at the city of Bantul, namely PES Jigudan, PES Gunturan, and PES Ciren collaborated. The data collection technique in this study was conducted by interviewing the principals of each school, observing the application of character education, and analyzing documents such as annual programs, teacher Lesson Plans, and school structures. Data were analyzed using the Miles & Huberman method, namely data reduction, data presentation, and conclusion. The results of this study are: 1) At the planning stage, PT. Astra International took part in the initial implementation meeting and explained the 4 pillars, one of which was the character pillar, 2) At the organizing stage, PT. Astra International handed over the division of tasks to schools where the character will be implemented with all the resources they have, 3) At the actuating stage, PT. Astra International supports programs owned by schools, both funding and notions, 4) In controlling and evaluation, PT. Astra International maintained intensive communication by occasionally visiting schools and closing with an evaluation meeting at the end of each year attended by all stakeholders.